Peran Kebijakan Ekonomi Biru dalam Pembangunan Perkotaan Berkelanjutan di Kota Tanjung Pinang - Hoki Apriyenson; Aria Bagiasa Chidmahdjati; Nefriwati Hilmi; Dea Rizky Saputri; Arie Afriadi; Zuleriwati A.S (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The implementation of blue economy policies in Tanjungpinang City, the capital of Riau Islands Province, aims to foster sustainable urban development by leveraging marine and coastal resources. This study explores the potential and opportunities of blue economy principles to enhance economic growth, social welfare, and environmental sustainability. Utilizing a qualitative approach, the research evaluates local government policy documents and collaborates with industry stakeholders to assess the impact of these policies. Findings reveal that Tanjungpinang’s strategic maritime location supports significant fishery production (118,661 tons in 2023) and tourism growth, creating jobs and reducing coastal poverty. Key programs include sustainable marine resource management, fishery processing industry development, human resource capacity building, market access optimization, eco-friendly infrastructure, and environmental policy enforcement. These initiatives promote ecological sustainability, economic value, and social inclusivity. However, challenges such as limited processing scales, resource continuity, and environmental pollution persist. The study underscores the need for coordinated governance, technological investment, and community participation to ensure long-term benefits. Tanjungpinang’s blue economy model offers a replicable framework for sustainable urban development in coastal regions.